Mapping Sustainability Preferences of West African Economic and Monetary Union. Case Study: Benin, Burkina Faso and Niger - Honorat Satoguina (Hamburg Institute of International Economics (HWWA), 2006)
This study discusses the concept of sustainability, in particular with respect to the CDM. In addition, based on cross-section interviews, the sustainability criteria for CDM projects in energy sectors in the studied countries are determined. These criteria could serve as a starting point for discussing and designing sustainable development criteria in the West African Economic and Monetary Union. Moreover, issues related to the location of Designated National Authorities (DNA) and their funding are investigated. Stakeholders prefer a multi-institutional DNA, and support governement co-funding of DNAs. As the studied countries lack the means to fund DNAs, we suggested the concept of a regional CDM approval body as discussed in Discussion Paper 352. This paper shows that countries' stakeholders advocate such a concept.
Keywords: D74; Q01; C80; L32; C82; L31; 330; Sustainable Development; Sustainability criteria; stakeholder behaviour; Crosssectional interview